(+)-Borneol inhibits neuroinflammation and M1 phenotype polarization of microglia in epileptogenesis through the TLR4-NFκB signaling pathway - Li, Shuo; Adamu, Alhamdu; Ye, Yucai; Gao, Fankai; Mi, Rulin; Xue, Guofang; Wang, Zhaojun (Frontiers in Neuroscience, 2024)
ObjectiveTo investigate the effect of (+)-borneol on neuroinflammation and microglia phenotype polarization in epileptogenesis and its possible mechanism.MethodsBased on mouse models of status epilepticus (SE) induced by pilocarpine, and treated with 15 mg/kg (+)-borneol, western-blot was used to detect the expressions of NeuN, Iba-1, TLR4, p65 and p-p65 in the hippocampus. Immunofluorescence was used to detect the expression of apoptosis-related proteins Bax and Bcl-2. To explore the effect of (+)-borneol on microglia in vitro, we used the kainic acid-induced microglia model and the concentration of (+)-borneol was 25 μM according to CCK-8 results. The levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-10 (IL-10) in the supernatant of each group was detected by ELISA. The nitric oxide (NO) content in the supernatant was detected by Griess method. The expressions of Iba-1 and TLR4-NFκB signaling pathway-related proteins (TLR4, p65, p-p65) were detected by Western-Blot. Immunofluorescence was used to detect microglia’s M1 and M2 phenotype polarization and the expression of Iba-1 and TLR4.Results(+)-borneol reduced hippocampal neuronal injury, apoptosis, and microglia activation by inhibiting the TLR-NFκB signaling pathway in SE mice. TLR4 agonist LPS partially reversed the neuroprotective effect of (+)-borneol. In the KA-induced microglia model, (+)-borneol inhibited microglia activation, M1 phenotype polarization, and secretion of pro-inflammatory cytokines through the TLR4-NFκB signaling pathway. LPS treatment inhibited the therapeutic effects of (+)-borneol.Conclusion(+)-borneol inhibits microglial neuroinflammation and M1 phenotype polarization through TLR4-NFκB signaling pathway and reduces neuronal damage and apoptosis in SE mice. Therefore, (+)-borneol may be a potential drug for epilepsy modification therapy.